Integration constant differential equations

Therefore, the constant of integration is: C=f (x)-F (x) =f (2)-F (2) =1-F (2) This is a simple answer, however for many students, it is very difficult to this this abstractly. So, let's look at a concrete

Solve Now Math app

Integrating Factor Method

It flows out of the second container at a constant rate. Let x (t) = volume in container 1; y (t) = volume in container 2. EQ 1: dx/dt = -ax EQ 2: dy/dt = ax - b, where a, b are constants.

  • Track Progress
  • Build bright future aspects
  • Always on Time
  • Enhance your academic performance
  • Track Improvement

Integration and Differential Equations

Technically when we integrate we should get, ∫ cos(1 +2x) +sin(1 +2x)dx = 1 2(sinu −cosu+c) ∫ cos ( 1 + 2 x) + sin ( 1 + 2 x) d x = 1 2 ( sin u − cos u + c) Since the whole

  • 256+ Math Experts
  • 6 Years on market
  • 52175 Completed orders

What do our customers say?

Solving Differential Equations with Integrating Factors

is called the constant of integration. It is easily determined that all of these functions are indeed antiderivatives of cos ⁡ ( x ) {\displaystyle \cos(x)} : d d x [ sin ⁡ ( x ) + C ] = d d x sin ⁡ ( x ) + d d x


Improve your scholarly performance

I am tracking my progress.

Solve mathematic problems

Save time

Call now and get service instantly!

Clarify math equation

Deal with math

One way to save time is to automate your tasks.

Deal with math tasks

Clarify math problems

If you're looking for a punctual person, you can always count on me.


Integrating factor

x 3 e y + x 2 y = K For the constant yes it absorbs the factor 2 and you can have it on the other side. Your result is correct but I wouldn't write the integrals you wrote 2 x 3 e y +

Differential Equations

the differential equation with s replacing x gives dy ds = 3s2. Integrating this with respect to s from 2 to x : Z x 2 dy ds ds = Z x 2 3s2 ds H⇒ y(x) − y(2) = s3 x 2 = x3 − 23. Solving for y(x) (and